Challenging Management of an Acute Traumatic Carotid-Cavernous Fistula in a 2-Year-Old Child with Literature Review - Solis, Frank; Macha, Luis; Toledo, Mauro; Gálvez, Ricardo; Ecos, Rosa (Indian Journal of Neurosurgery, 2023)
Traumatic carotid-cavernous fistula (TCCF) is a rare occurrence in the pediatric population. However, the neurological sequelae of TCCF are associated with higher morbidity and mortality in pediatric patients. We report the case of a 2-year-old child with TCCF treated at a public hospital in Peru. The etiology of the injury was due to a fall of approximately 5 meters. The diagnosis was made based on the clinical picture and neuroimaging findings. The initial proposed treatment was performed with the hope of preserving the parent artery; however, due to persistence of the TCCF, embolization of the parent artery with coils and embolizing substance was performed. A literature review of similar cases was performed and identified eight cases in children under 10 years of age. Endovascular management of an acute TCCF is a challenge due to the high morbidity and mortality during the acute phase and can be complicated when other traumatic injuries are present. Maintaining the parent artery is important; however, when this is not possible, trapping the parent artery may provide an alternate option when appropriate collaterals exist.
Keywords: traumatic carotid-cavernous fistula; type A fistulas; embolization